Relationships Among Character Strengths, Self-efficacy, Social Support, Depression, and Psychological Well-being of Hospital Nurses - Jianfei Xie; Min Liu; Zhuqing Zhong; Qiuxiang Zhang; Jianda Zhou; Lu Wang; Keke Ma; Siqing Ding; Xiaohong Zhang; Qian Sun; Andy S.K. Cheng (Elsevier, 2020)
Purpose: From the perspective of positive psychology, our study aimed to explore depressive symptoms and psychological well-being among Chinese nurses, as well as analyze the impacts of character strengths, self-efficacy and social support on the mental health of nurses. Methods: A cross-sectional and descriptive design using five self-reported questionnaires was used to investigate a cohort of 4238 nurses during 2018. A structural equation modeling analysis was used to verify a hypothetical model linking character strengths, self-efficacy, social support, depressive symptoms, and psychological well-being. Results: The prevalence of depression among this cohort of Chinese nurses was 58.1%. The mean scores for caring, inquisitiveness, and self-control were 19.93 (SD = 2.82), 15.94 (SD = 3.00), and 16.34 (SD = 2.95), respectively. The hypothesized model was a good fit of the data (χ2/df = 1.77, p = .183, root mean square error of approximation = 0.04, goodness of fit index = 1.00, comparative fit index = 1.00, Tucker-Lewis index = 1.00). Except for the path from self-control to depression, the other hypothetical paths investigated were statistically significant. Conclusion: Character strengths were directly and positively associated with psychological well-being. Inquisitiveness was the strongest direct protective factor for depression. In addition, character strengths indirectly alleviated depression and increased psychological well-being through mediating variables of social support and self-efficacy. This study should alert nurse managers that more attention should be paid to the character strengths and mental health of nurses. This study provides evidence for interventions based on character strengths as a management strategy to support the mental health of nurses.